NURSES’ PERSPECTIVES ON THE DEGREE OF MISSED NURSING CARE IN THE PUBLIC HOSPITALS IN HAIL CITY, KINGDOM OF SAUDI ARABIA - Mohammed Hamdan Alshammari; Haidee Pacheco; Eddieson Pasay-an; Farhan Alshammari; Abdalkareem Alsharari; Ebaa Felemban; Richard Dennis Dayrit (Belitung Nursing Journal, 2020)
Background: Literature suggests that merely omitting nursing care can put patients in danger and that avoiding these omissions potentially prevents deaths in hospitals. Objective: This study aimed to determine the perspective on the degree of missed nursing care among hospital nurses as it relates to their demographic profile. Method: A quantitative comparative research design was employed in this study. The study was conducted in the public hospitals in Hail City, Kingdom of Saudi Arabia. The study participants were 317 staff nurses, chosen through a simple random sampling, from the public hospitals of Hail City. Data were collected through a self-administered questionnaire between February and June of 2019. Results: The overall mean of the participants’ reported scores was “never missed” at 4.62. Statistically significant results were found in terms of the number of children (0.001), years of experience (0.004), unit of assignment (0.001), and the level of satisfaction with the profession (0.001). All other variables such as gender, age, marital status, and shift were found insignificant, where all of the p-values were more than 0.05. Conclusion: Nurses who had more children, a greater lack of experience, were assigned to a complex unit, and were less satisfied in the profession were more likely to miss nursing care. As such, these errors can compromise the outcomes of nursing care in hospitals.